Conjugal Transfer of Bacteriophage Resistance Determinants on pTR2030 into Streptococcus cremoris Strains - Sing, Wesley D. (1986)
Agar surface conjugal matings were used to introduce heat-sensitive phage resistance (Hsp(+)) determinants carried on the conjugal plasmid pTR2030 into Streptococcus cremoris KH, HP, 924, and TDM1. Lactose-fermenting (Lac(+)) transconjugants were selected from matings of Lac(−) variants of S. cremoris KH, HP, 924, and TDM1 with Streptococcus lactis ME2 or a high-frequency donor, S. lactis T-EK1 (pTR1040, Lac(+); pTR2030, Hsp(+)). For all of the S. cremoris strains examined, select Lac(+) transconjugants were completely resistant to plaquing by their homologous lytic phages. In all cases the plaquing efficiencies were less than 10(−9). Acquisition of a 30-megadalton plasmid (pTR2030) in the S. cremoris phage-resistant transconjugants was demonstrated by direct plasmid analysis, by hybridization with (32)P-labeled probes, or by conjugal transfer of pTR2030 out of the phage-resistant transconjugants into a plasmid-cured recipient, S. lactis LM2302. Acid production, coagulation ability, and proteolytic activity of phage-resistant transconjugants in milk were comparable to those of their phage-sensitive parents. Further, S. cremoris phage-resistant transconjugants were not attacked by phage in starter culture activity tests, which included a 40°C incubation period. The results demonstrated that phage resistance determinants on pTR2030 could be conjugally transferred to a variety of S. cremoris strains and confer resistance to phage under conditions encountered during cheese manufacture. Phage-resistant transconjugants of S. cremoris M43 and HP were also constructed without the use of antiblotic markers to select conjugal recipients from mating mixtures.